Register Of Twitter Language Variety In The Social Media Twitter - Nilam Setiawati (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2023)
At this time the development of technology is very rapid, especially for teenagers. Today's social media users are excelled by teenagers which has led to a wide variety of languages on social media, one of which is Twitter. Twitter is a social media where we can find lots of things, from fashion, food to hot news. And because many people use Twitter and Twitter is seen as social media with open-minded users, many Twitter languages are formed that only Twitter users can understand. This research will discuss the phenomenon of the language used by Twitter users, from teenagers to those who are already married. The source of the data comes from the representatives of Twitter users. This research method is descriptive-qualitative, so data collection is done by notetaking techniques. Based on the data found, there are 10 kinds of languages used by people who use Twitter social media, one of which is like ACC which means account, ATM which means at the moment, JB which means join together, JFB which means promise to follow back, mutual which means friends and NDER which means the sender or sender of a thread or tweet.